Puss in boots (Hollywood, CA Paramount Home Entertainment, 2012)
You loved him in Shrek, now see where the one and only swashbuckling feline found his fame. Lover, fighter, and outlaw Puss in Boots is off on the adventure of his nine lives as he teams up with Kitty Softpaws and Humpty Dumpty for the ultimate showdown with the notorious Jack and Jill . Here's the true story of the Cat, the Myth, the Legend - Puss in Boots!
Blu-ray
Directed by Chris Miller.
Amy Sedaris, Antonio Banderas, Billy Bob Thornton, Salma Hayek, Zach Galifianakis.
MPAA rating: PG.
English, French, Spanish audio; English, French, Spanish subtitles.
111814
Keywords: Children's films; Animated films; Films pour enfants